The effect of servant leadership on service quality: An applied research in the Babylon Water Directorate - Shaaban, Haider Ali; Mohammed, Atheer Abdullah (The journal of contemporary issues in business and government, 2021)
The current research deals with two important variables, which are servant leadership as an independent variable, and service quality as an approved variable, and the purpose of the research is to know whether there is an effect of servant leadership on the quality of the service provided and what is the relationship between them, and there are (150) individuals representing the research sample out of a total of 230 individuals, represented by employees and leaders Central in the Babylon Water Directorate. The questionnaire was used as a basic tool for data collection and included (50) items, and ready-made measurements were used in preparing the items. Questionnaire, and after evaluating and testing the reliability of the study measurement tools, the researcher conducted data analysis and hypothesis testing using advanced statistical tools and analyzed them through the statistical program (SPSS V.26). As the research found a positive impact between the dimensions of servant leadership and service quality in the research organization. The research concluded with a set of recommendations for the research body to improve the quality of service provided to citizens.